Coding and encoding rights in internet infrastructure - Stefania Milan; Niels ten Oever (Internet Policy Review, 2017)
This article explores bottom-up grassroots ordering in internet governance, investigating the efforts by a group of civil society actors to inscribe human rights in internet infrastructure, lobbying the Internet Corporation for Assigned Names and Numbers. Adopting a Science and Technology Studies (STS) perspective, we approach this struggle as a site of contestation, and expose the sociotechnical imaginaries animating policy advocacy. Combining quantitative mailing-list analysis, participant observation and qualitative discourse analysis, the article observes civil society in action as it contributes to shape policy in the realm of institutional and infrastructure design.
Keywords: 300; Internet Corporation for Assigned Names and Numbers (ICANN); Civil society; Human rights; Sociotechnical imaginaries; Bottom-up design